Computer and remote‐sensing infrastructure to enhance large‐scale testing of individual‐based forest models. Issue 9 (1st November 2015) - Shugart, Herman H; Asner, Gregory P; Fischer, Rico; Huth, Andreas; Knapp, Nikolai; Le Toan, Thuy; Shuman, Jacquelyn K
Abstract : Global environmental change necessitates increased predictive capacity; for forests, recent advances in technology provide the response to this challenge. "Next‐generation" remote‐sensing instruments can measure forest biogeochemistry and structural change, and individual‐based models can predict the fates of vast numbers of simulated trees, all growing and competing according to their ecological attributes in altered environments across large areas. Application of these models at continental scales is now feasible using current computing power. The results obtained from individual‐based models are testable against remotely sensed data, and so can be used to predict changes in forests at plot, landscape, and regional scales. This model–data comparison allows the detailed prediction, observation, and testing of forest ecosystem changes at very large scales and under novel environmental conditions, a capability that is greatly needed in this time of potentially massive ecological change.